1995
DOI: 10.1177/014860719501900155
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate and Metabolic Response to Burn Injury in Humans

Abstract: In burn patients, variability in heart rate is associated with a significant part of postburn hypermetabolism variability. Therefore, heart rate may be considered a useful variable to be used for the evaluation of the energy requirements of severely burned patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Therefore, a change in the extrinsic intake of one of the substrates affects the measured EE. In certain patient populations, as burns, the % of the initial BSA burn [33,37,38,86,106,107,109,110] and the post burn day [37,107,109,110] were associated with energy expenditure, however, the % open burn wound after therapy is initiated is not useful as a predictive factors of EE. This relationship could be explained by the underlying inflammatory and hormonal process that is triggered by the initial burn insult and its evolution across ICU days [111].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, a change in the extrinsic intake of one of the substrates affects the measured EE. In certain patient populations, as burns, the % of the initial BSA burn [33,37,38,86,106,107,109,110] and the post burn day [37,107,109,110] were associated with energy expenditure, however, the % open burn wound after therapy is initiated is not useful as a predictive factors of EE. This relationship could be explained by the underlying inflammatory and hormonal process that is triggered by the initial burn insult and its evolution across ICU days [111].…”
Section: Discussionmentioning
confidence: 96%
“…Fourth, this study identified several factors with no association with EE. These factors were heart rate [34,58,63,70,83,90,92,95,106,116,118,137], FiO 2 [70,90,91,138], respiratory rate [70,90,95], respiratory disease diagnosis [22,70,90], PEEP [90,138], CRP [23,52,59,91,134], size [22,51,74,109], and ICU days [22,23,113,116]. Physiologically, heart rate changes and inflammation represented by CRP result in a change in oxygen consumption and hence EE.…”
Section: Discussionmentioning
confidence: 99%
“…That said, some findings indicate that the beta-adrenergic receptors are involved in regulating the phenotype of white adipose tissue in humans. Patients with burn trauma and pheochromocytoma (adrenal gland tumour) secrete excessive amounts of catecholamines that activate beta-adrenergic receptors (Jeschke et al 2008;Frontini et al 2013;Sidossis et al 2015) and markedly accentuate metabolic rate (McCullagh & Engel, 1942;Giantin et al 1995), due at least in part to augmented triglyceride-fatty acid cycling (Wolfe et al 1987). Because of the excessive thermogenesis and hence highly negative energy balance, these conditions lead to significant loss of both fat (Petrák et al 2013;Porter et al 2016b) and lean mass (Lee et al 2019).…”
Section: Beta 2 -Adrenergic Stimulation Of Brown Adipocytesmentioning
confidence: 99%
“…The extent of thermal injury (%BSAB) has been suggested as a primary influencing factor by numerous investigators and, as a result, has been included in their predictive methods. 1,28,31,32,35,36,[38][39][40][41][42][43][44] The more recent publications suggest a maximum MEE of about twice that of basal. 3,35,36,38 Our data corroborate these findings as none of the patients exceeded hypermetabolism beyond 207% of predicted by the Harris Benedict equations.…”
mentioning
confidence: 99%